Exchange Rate Pass-Through and Monetary Policy in Croatia - Bonato, Leo.; Billmeier, Andreas (Washington, D.C. : International Monetary Fund, 2002)
Exchange rate targeting is considered the best policy option in dollarized economies when wages and prices are indexed to the exchange rate. Croatia is a highly dollarized economy, but empirical investigation conducted in this paper shows that exchange rate pass-through has been low after stabilization. This finding, which is robust to different methodologies (VAR, cointegration), would suggest that dollarization is mostly limited to financial assets and therefore that strict exchange rate targeting may not necessarily be the best option. However, policy implications are unclear due to the endogeneity of the pass-through to the policy regime.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet